(untitled) (Lapai Journal of Economics, 2024)
Nigeria is a nation of contradictions; it is a rich nation with poor people and there is widespread poverty amidst plenty. This study examined the relationship of selected macroeconomic variables (inequality, unemployment, inflation and fertility rate) with poverty in Nigeria for the period 1991 to 2022. It made use of Autoregressive Distributed Lag regression method and Granger causality test. The result shows that fertility as well as lagged values of inflation and unemployment are significantly related to poverty but inequality does not. In addition, out of these variables, it is only unemployment that Granger causes poverty and the relationship is weak. Consequently, it was concluded that fertility has significant impact on poverty in Nigeria; unemployment and inflation have delayed but significant impact on poverty, and poverty has significant impact on both fertility and unemployment. Inequality has no significant relationship with poverty. In line with the findings, it was recommended that poverty reduction strategies that emphasizes fertility education, labour intensive investment strategies and entrepreneurship development should be prioritized by relevant development actors such as the government and Civil Society Organisations.